2017
DOI: 10.18632/oncotarget.15433
|View full text |Cite
|
Sign up to set email alerts
|

Tumor stage and primary treatment of hepatocellular carcinoma at a large tertiary hospital in China: A real-world study

Abstract: The current clinical reality of tumor stages and primary treatments of hepatocellular carcinoma (HCC) is poorly understood. This study reviewed the distribution of tumor stages and primary treatment modalities among a large population of patients with primary HCC. Medical records of patients treated between January 2003 and October 2013 for primary HCC at our tertiary hospital in China were retrospectively reviewed. A total of 6241 patients were analyzed. The distribution of Barcelona Clinic Liver Cancer (BCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…In China, about half of HCC patients are diagnosed as HCC in an advanced stage [2] . Many studies compared the safety and efficacy of hepatectomy to transarterial chemoembolization [3,23,24] .…”
Section: Should Postoperative Hcc Patients Receive Adjuvant Treatmmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, about half of HCC patients are diagnosed as HCC in an advanced stage [2] . Many studies compared the safety and efficacy of hepatectomy to transarterial chemoembolization [3,23,24] .…”
Section: Should Postoperative Hcc Patients Receive Adjuvant Treatmmentioning
confidence: 99%
“…HBV and HCV infections, alcohol consumption, non-alcoholic steatohepatitis cirrhosis, or obesity pandemic are risk factors of HCC development. A recent survey study found about 70% patients with HCC are diagnosed as intermediate or advanced disease because of the lack of significant syndrome in their early stage [2] . Main treatments of HCC include hepatectomy, liver transplantation, ablation (radiofrequency, microwave, cryoablation), transarterial chemoembolization, radiotherapy, chemotherapy, target therapy, and so on.…”
mentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is very likely to invade the intrahepatic vessel, especially the portal vein, thus forming the portal venous tumor thrombus (PVTT) . It is reported that the incidence of PVTT is 44%‐62.2% . PVTT is one of the important biological characteristics and poor prognostic factors of HCC .…”
Section: Introductionmentioning
confidence: 99%
“…1 It is reported that the incidence of PVTT is 44%-62.2%. 2 PVTT is one of the important biological characteristics and poor prognostic factors of HCC. 3 Transcatheter arterial chemoembolization (TACE) is one of the most common treatments for advanced HCC patients with PVTT.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only a small proportion of patients with HCC are with early stage HCC [2]. Hepatic resection, radiofrequency ablation, and percutaneous ethanol injection are curative treatments for such patients [3].…”
Section: Introductionmentioning
confidence: 99%